Recruitment of a Population‐Based Sample of Young Black Women with Breast Cancer through a State Cancer Registry. Issue 2 (14th December 2015) - Bonner, Devon; Cragun, Deborah; Reynolds, Monique; Vadaparampil, Susan T.; Pal, Tuya
Abstract: Given that Black women remain underrepresented in clinical research studies, we sought to recruit a population‐based sample of young Black women with breast cancer through a state cancer registry. Demographic and clinical information on all Black women diagnosed with invasive breast cancer at or below age 50 between 2009 and 2012 in Florida was obtained through the state cancer registry. Survivors were invited to participate in the study through state‐mandated recruitment methods. Participant demographic and clinical characteristics were compared using Chi‐squared tests for categorical variables and the two sample t ‐test for continuous variables to identify differences between: (i) consented participants versus all other eligible; and (ii) living versus deceased. Of the 1, 647 young Black women with breast cancer, mean age at diagnosis was 42.5, with the majority having localized or regional disease, unmarried, privately insured, and employed. There were no significant differences in demographic and clinical variables between the 456 consented study participants versus the remaining 1, 191 presumed eligible individuals. Compared to potential participants, women determined to be deceased prior to recruitment ( n = 182) were significantly more likely to have distant disease and a triple‐negative phenotype. They were also significantly more likely to be unemployed, and uninsured or have public insurance (i.e., Medicaid or Medicare). Our results demonstrate that recruitment of a population‐based sample of breast cancer survivors through a state cancer registry is a feasible strategy in this underserved and underrepresented population. However, survival bias, which was observed due to the lag time between diagnosis and recruitment, is important to adjust for when generalizing findings to all young Black breast cancer patients.